The effect of intellectual capital and shariah supervisory boards on social performance of Islamic banks / Bima Cinintya Pratama, Amrizah Kamaluddin and Shukriah Saad - Pratama, Bima Cinintya; Kamaluddin, Amrizah; Saad, Shukriah (Universiti Teknologi MARA, 2021)
This study examined Islamic banks' social performance by considering Intellectual Capital (IC) and Shariah Supervisory Boards (SSB) as antecedents. More specifically, it examined the antecedents that can exert the role of IC and governance mechanism of SSB in enhancing Islamic banks' social performance. Therefore, this study empirically analyzed the effect of IC and SSB on social performance in Indonesian Islamic banks with a sample of 14 Islamic banks throughout the period 2008-2019. To test the research hypotheses, panel data regression model analysis was applied. The results did not establish a positive impact of intellectual capital on the banks' social performance. This result indicated that the size of intellectual capital might not lead to better social performance. This outcome may be due to IC still being the focus of financial performance such that it has not been utilized to optimize the social performance of Islamic banks. The results also showed that SSBs have a positive effect on social performance. It can be concluded that Supervisory Boards could monitor the social activities conducted by Islamic banks, leading to an improvement in the activities. This study helps to bolster the understanding of the role of IC and SSB governance in enhancing the social performance function of Islamic banks.